2009
DOI: 10.1063/1.3097011
|View full text |Cite
|
Sign up to set email alerts
|

Observation of ultraviolet emission and effect of surface states on the luminescence from tin oxide nanowires

Abstract: Ultraviolet (UV) and orange emissions have been observed from vapor-liquid-solid grown SnO2 nanowires. From the luminescence, the donor and acceptor binding energies have been estimated. The dependence of the orange luminescence on the diameters of tin oxide nanowires has been observed and the wavelength of the UV luminescence is found to depend on the laser power. Both the shift in the UV and the intensity of the orange luminescence is found to be dependent on the surface states of the tin oxide nanowires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 8 publications
7
48
1
Order By: Relevance
“…Their calculations showed that occupied levels associated to the vacancy appeared at about 1 eV above the top valence band. Many researchers also inclined to assign the origin of deep-level luminescence in SnO 2 to oxygen vacancies [21,27,28]. In Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Their calculations showed that occupied levels associated to the vacancy appeared at about 1 eV above the top valence band. Many researchers also inclined to assign the origin of deep-level luminescence in SnO 2 to oxygen vacancies [21,27,28]. In Fig.…”
Section: Resultsmentioning
confidence: 98%
“…However, the theoretical band gap of SnO 2 was calculated to be direct as shown in Ref. [16] and many investigations were performed on the basis of its direct band gap transition [17][18][19]. Therefore, we chose the direct band gap transition in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the reports in literature suggested a dominant broad photoluminescence (PL) peak in the visible range, [17][18][19][20][21][22][23][24][25] whereas others revealed the existence of UV emission in SnO 2 . [26][27][28][29][30][31] Thin films are indispensable for device applications, but there have been only a few works so far on the optical properties of SnO 2 thin films. 32,33 Until now, light emission in SnO 2 and the related mechanisms have remained as an issue of debates, and there is also a paramount need for theoretical insights.…”
Section: Introductionmentioning
confidence: 99%